Fluctuation of Spuriously Elevated Troponin I: A Case Report. (7th June 2012) - Ghali, Sam; Lewis, Keith; Kazan, Viviane; Altorok, Neezam; Taji, Jamil; Taleb, Mohammad; Lanka, Kiranmayee; Assaly, Ragheb
Abstract : Serum troponin is a useful laboratory study for the diagnosis of acute myocardial infarction. However, elevations can also be seen in a variety of other diseases processes. Falsely positive troponin values caused by interference with current troponin assays have been reported. We report a unique case that demonstrates the fluctuation of falsely elevated troponin correlating with hemoglobin, serving as a marker of heterophile antibody levels. A 74-year-old gentleman presented to our Emergency Department with a several-day history of increasing shortness of breath associated with a new-onset chest pain and a troponin I level of 77.28 ng/mL. Throughout his stay, fluctuations in measured troponin levels correlated strongly with fluctuations in hemoglobin levels. Several investigations confirmed false elevated troponin levels secondary to heterophile antibody interference. We conclude that hemoglobin trending in our patient represented a surrogate measure of his heterophile antibody titers with time and that fluctuations in these levels correlated with respective fluctuations in the falsely elevated troponin levels.